STRUCTURE OF REVENUE AND EXPENDITURE OF FISHERMEN HOUSEHOLD IN SOUTH KAUR SUBDISTRICT KAUR DISTRICT - Bambang Sumantri; Melli Suryanty; Reki Susanti (Badan Penerbitan Fakultas Pertanian (BPFP), 2019)
This study aims to determine the structure of fishermen household income and expenditure. This research was conducted in March-April 2018 in Sekunyit Village. Research location is determined by purposive with Sekunyit consideration that in the village is one of the fishing villages in the Kaur district. Data processed using analysis of receipts and expenditures of households. The results showed the average amount of fisherman household income in Sekunyit Village was Rp. 8,606,594,59 / month. Revenue from the capture fisheries sector contributed the most (82.08%) to the fishermen household income. Meanwhile, the average expenditure of a fisherman's household in Sekunyit Village is Rp. 3,980,499 / month , where 69.24% was used to finance the capture fisheries business sector.